Problematika Penerapan Diversi Terhadap Anak Pelaku Tindak Pidana Narkotika - Irwan Irwan (Universitas Islam Indonesia, 2020)
This study examines, first, the application of diversion in narcotics crimes committed by children after the enactment of Perma No.4 of 2014 on Guidelines for the Implementation of Diversion in the Juvenile Justice System (SPPA Law); second, the constraints on the application of diversion in narcotics crimes committed by children after the enactment of Perma No. 4 of 2014. This is a normative legal research supported by information from sources using statutory and conceptual approach and analyzes it from a perspective. The results of the study conclude that, first, the application of diversion in narcotics crime according to Perma No. 4 of 2014 has not been implemented. Based on the SPPA Law, the application of diversion can be carried out in cases where the threat is under 7 (seven) years while in Perma No. 4 of 2014 the application of diversion can be carried out for cases where the threat is more than 7 (seven) years but the charges are subsidarity, alternative, or cumulative. One of the charges is that there is a threat of diversion under 7 (seven) years. Second, law enforcers think that narcotics is a criminal offense that is highly charged even though the charges are alternative, where Perma No. 4 of 2014 requires diversion in criminal acts charged with alternative charges, this happens because law enforcers rarely use Perma No. 4 of 2014.